Mechanism study and determination kinetic of catalytic oxidation of mercaptans in Merox process - Kazem Motahari, PhD; Mohammad Abdollahi-Moghaddam; Ali Rashidi (South African Journal of Chemical Engineering, 2020)
Sulfur-containing pollutants lead to reduced quality of end products and environmental problems. Mercaptans are one of those sulfur pollutants which not only are smelly and toxic but also have high corrosive property. Mercaptan catalytic oxidation is the most important method of oil production refining from mercaptan. Thus, cognition of the reaction kinetics and interrogation of effects of various factors on the process are of the most requirements of mercaptan removing units. Due to the inadequate efforts made on reaction kinetics determination of catalytic oxidation of light mercaptans available in liquefied petroleum gas (LPG), this study was done in this regards. First, rate-determining step (RDS) of reactions was determined by analyzing the experimental data obtained from the Merox unit. The experiments were carried out on a cobaltphthalocyanine liquid catalyst in a packed reactor. In order to better understand the process, design, and optimization, the kinetics were defined with respect to the limiting reaction. By investigating the effective parameters of the kinetics, it was determined that the mercaptide ion (RS-) confines the oxidation reaction rate and has the first order in the rate equation. Finally, optimal values were proposed for each of the parameters.